SOME CONCLUSIONS DRAWN FROM A BASINAL ANALYSIS OF THE ECCA SERIES IN THE KARROO BASIN - Ryan, P. J. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1968)
This is a summary of a study made of the Ecca and lowermost Beaufort rocks in South Africa with particular reference to the distribution of the various facies and their relationship to palaeocurrent trends. As a result of this the Ecca can be divided into four distinct facies, called the Northern, Southern, Western and Central Facies. The lowermost Beaufort is represented by sediments having the same distribution and origin as the first three facies of the Ecca. The maximum thickness of sediments described here is 11,000 feet.